Building an E-Learning System Calculating Pension Funds Using the Cox Ingersoll Ross Interest Rate Model - Nerli Khairani; Elfitra Elfitra; Tiur Malasari Siregar (Postgraduate, University of Mataram, 2025)
Pension funds play a crucial role in ensuring financial security in retirement, yet many individuals struggle with understanding and accurately calculating their future pension benefits. This research aims to provide an interactive learning platform that allows users to understand and calculate pension fund projections more accurately, by integrating the Cox Ingersoll Ross (CIR) interest rate model into the e-learning system, so as to improve users' financial literacy, especially in retirement planning. This study uses a Research and Development (R&D) approach with the ADDIE method, data through research instruments such as pre-test and post-test questionnaires, system usability assessment forms, semi-structured interview guides, and system usage observation sheets, which are then analyzed using descriptive and inferential statistical methods for quantitative data and thematic analysis for qualitative data. The results show the creation of an effective and user-friendly e-learning system for calculating pension funds, with the successful implementation of the Cox Ingersoll Ross interest rate model into the system, which resulted in a significant increase in user understanding of the concept of pension funds and the use of the CIR model. The developed e-learning system has proven effective in improving user understanding of pension fund calculations, with the use of the Cox Ingersoll Ross interest rate model providing more accurate and realistic projections, thus contributing significantly to improving user financial literacy, especially in the aspect of retirement planning.